Adoption of Beekeeping among RuralWomen in Samastipur District of Bihar - Anuradha Ranjan Kumari, Meera Singh (Indian Journal of Extension Education, 2022)
The present investigation was carried out to study the impact of training on adoption of beekeeping by rural women. Seven villages were selected purposively fromPusa block of Samastipur district in Bihar.Atotal of 50 trained and 50 untrained women were selected randomly. Data were collected from100 respondents with the help of interview schedule.The result revealed that maximum 88 per cent of trained women adopted beekeeping technology and ’t’ value of difference between the mean of two samples (27.8487**) was found significant at 1 per cent level of siginficance indicating a significant impact of beekeeping training on adoption of ruralwomen